Improving the mass transport of copper-complex redox mediators in dye-sensitized solar cells by reducing the inter-electrode distance. Issue 47 (28th November 2017) - García-Rodríguez, Rodrigo; Jiang, Roger; Canto-Aguilar, Esdras J.; Oskam, Gerko; Boschloo, Gerrit
Abstract : Reduction of inter-electrode distance in DSCs with copper-based electrolyte increases the photocurrent and fill factor by improving internal transport. Abstract : In this work, we study the influence of the distance between electrodes on the performance of dye-sensitized solar cells based on TiO2 using the organic dye LEG4 and a Cu(dmp)2 redox couple (dmp = dimethyl phenantroline). The solar cells are characterized by a large open circuit voltage of up to 1.03 V, and an efficiency of 8.2% has been achieved for a 5.3 μm thick TiO2 film using an epoxy resin-based sealed cell configuration with a minimal separation between electrodes. Transient short-circuit photocurrent measurements up to an intensity of 3 Suns show a significant decay in photocurrent after an initial peak current upon switching on the light for larger distance, resulting in a lower steady state photocurrent. For the smaller distance cells, the steady state photocurrent is linear with light intensity up to 2 Suns. Charge extraction measurements under short-circuit conditions show that reducing the distance between electrodes increases the electron collection efficiency and thus, the attainable photocurrent. Recombination losses increase with larger electrode separation distance and higher light intensity due to mass transport limitation of the redox mediator. Electrochemical impedance measurements confirm the effect of electrode distance on the redox couple transport, showing an additional loop with increasing distance. For the configuration where the TiO2 film is in very close proximity to the PEDOT-covered counter electrode, inductive behavior is observed at low frequencies. The inductive behavior disappears with the incorporation of an insulating porous ZrO2 layer. The equivalent circuit for the solar cell has been expanded to include this effect.